An Empirical Study of Middle-income Farmers on Millet Production in Kano South Nigeria: A Stochastic Frontier Analysis Approach - Khondaker, M E A; Baba, M U (International Journal of Statistical Sciences, 2023)
This paper aimed at assessing the technical efficiency of millet farmers in Kano south Nigeria using the stochastic frontier production function from the parametric perspective. The determinants of technical efficiency, such as, education, extension access, access to loans, farm size, labour etc, which played a great role in technical efficiency level, are assessed to measure the level of efficiency of the middle-income farmers. 227 middle income farmers were selected for the study and provide an empirical analysis of the efficiency determinants which aim to find a way of improving the millet production and productivity. The results show that middle income farmers’ productivity is very weak ranging from 0.023t/ha to 5.62t/ha, averaging 1.07t/ha. While the technical efficiencies of middle-income farmers range from 0.013 to 0.930 with mean of 0.621. However, the results also indicate that most of the above determinants have negative effect on technical efficiency for the farmers. So, there is need by the government at all levels to review the existing agricultural policy that will favour the reality on the ground which will result in improving the output level of the middle-income farmers with their minimum available input. International Journal of Statistical Sciences , Vol. 23(2), November, 2023, pp 39-46